The Early Childhood Development through Puzzle Games Viewed from Neuroscience Theory and Al-Qur'an - Anshori, Irfan; Syafe'i, Imam; Zahrotunnisa, Elsa Nabila (CV. Creative Tugu Pena, 2024)
The aim of this research is to identify the relationship between Neuroscience and child development by linking the game learning modelPuzzle. This research was conducted at PAUD Darel Azhar; the Jl.Education Complex 08/09, Muara Ciujung Timur Village, Rangkasbitung District, Lebak Regency, Banten Province, 42314. The method used is a qualitative method. Data collection techniques include observation, interviews and documentation. Interviews were conducted on certain objects that were closely related to this research; such as teachers, parents and students. The data analysis technique used begins with organizing and preparing the data; understand all research data; interpret the data and then draw conclusions. The results of this research explain that the relationship between neuroscience and child development is influenced by the stimulation given to children. Puzzle games are a form of stimulation for the growth of children's brain cells. Neuroscience in the Qur'an is mentioned asthinking, thank you, tadabur, andtabashshurNeuroscience from the perspective of Islamic educational thought is mentioned in the metaphysics of al-Ghazali, al-Farabi and Ibn Sina. Neuroscience in child development can foster high discipline values, want to try new things, have special value for children and have a high sense of curiosity; and all of this is a form of providing stimulation by using puzzle games for children. Keywords: Early Childhood, Neuroscience, Puzzle Games